Dissimilar Pain of Primary Epiploic Appendagitis and Malabsorption - Wolfgang J Schnedl (Journal of Clinical and Diagnostic Research, 2017)
Primary Epiploic Appendagitis (PEA) is a rare cause of acute or subacute abdominal complaints and non-migratory pain. Usually the diagnosis of PEA is made when Computed Tomography (CT) reveals characteristic figures. Nonspecific abdominal complaints including diffuse abdominal pain may be caused by carbohydrate and/or protein malabsorption. We report a case of a patient with PEA who recovered without medication or surgical treatment within a few days. Eight months later, he was diagnosed with lactose- and histamine malabsorption and Helicobacter pylori infection. The malabsorption was treated successfully with an individually-tailored diet free of culprit triggers and the Helicobacter pylori infection was eradicated. A localized non-migratory abdominal pain caused by PEA needs to be differentiated from nonspecific abdominal complaints due to malabsorption and Helicobacter pylori infection.